디지털 취약계층인 소상공인 보호를 위한 광고산업진흥법의 역할과 사회적 지원 체계 연구 - 박정섭; 장석권 (사회복지법제연구, 2025)
광고 시장은 온라인광고를 중심으로 지속적으로 성장하고 있으며, 온라인광고 시장은 디지털 취약계층인 소상공인이 주요 광고주로 자리매김하고 있다. 기존 방송광고등에 비하여, SNS, 블로그, 지도 등을 활용하여 소상공인이 더 쉽게 접근할 수 있는구조이다. 그러나 광고 산업 관련 통합법은 없으며, 표시·광고법에서 광고 전반의 표현에 대한 규제를 하는 수준에 그치는 상황이다. 품목별로도 건강기능식품의 기능성규제 등 표현, 게재방식 등에 한하여 제한적으로 규정하고 있을 뿐, 광고 산업에 대한진흥 및 규제 체계 전반에 대한 규정은 전무하다. 이에 한국광고총연합회를 중심으로 광고산업진흥에 관한 법률 제정을 추진해왔으며, 2024년 6월 18일 김승수 의원 대표 발의로 「광고산업진흥법」이 발의되었다. 「광고산업진흥법」은 제정 이유에서 “광고산업은 21세기 우리나라의 성장동력을 이끌 수 있는 산업으로서 국내 광고시장은 19조원이 넘는 규모를 형성하고 있음. 광고산업은 단순한 상품 판매 수단이나 마케팅의 하위 요소에 머무르는 수단이아니라 다양한 미디어 산업의 재정적 존립기반이 되는 핵심산업이며, 문화콘텐츠의 중요한 분야로 성장하고 있는 문화산업이기도 함. 그러나, 광고산업을 정의하고 체계적이며 총괄적으로 지원할 수있는 기본 법률이 없어 조사ㆍ연구, 인력 양성, 공정한 유통환경조성이나 산업 생태계 보호 등 산업 진흥체계 마련에 대한 시장과 업계의 요구가 높아지고 있는 상황임. 이에 광고산업 진흥을 위한 기본적인 사항을 규정하여 광고문화를 진흥하는 기반을 마련함과 동시에 디지털 기술 발전, 글로벌화 등시장 변화에 능동적으로 대응하고 시장 수요에 맞는 전문인력 육성 및 중소형 광고회사 지원을 통해건강한 산업 생태계를 조성함으로써 산업 경쟁력을 강화하고 국민경제 발전에 이바지하려는 것임.”이라고 밝히면서, 광고 산업 전반에 대한 활성화 및 건전화 체계 구축을 목적으로 하고 있음을 설명하고 있다. 광고 관련 법률이 산재되어 있고, 표시광고법이 광고의 표현물에 한정된 규제 중심의 법률이라는 점에서 광고 산업의 육성을 목적으로 하는 법률은 적극 추진되어야 한다. 특히 인터넷 산업의 플랫폼들의 수익 모델이 대부분 쇼핑과 광고이므로, 광고 산업의 성장은 IT 산업의 성장동력이다. 또한 SNS가 대중화된 시장에서 광고와 정보는명확히 구분되지 않으며, 소비자 입장에서도 광고가 정보로서의 역할을 충분히 하고있으므로, 광고 산업의 성장을 도모하는 것은 국가 경제 및 소비자 이익 측면에서도긍정적이라고 보여진다. 다만, 현행의 광고산업진흥법은 광고 사업자 중심의 규정으로 되어 있으며, 광고 시장의 가장 큰 규모를 차지하고 있는 온라인광고에 대한 규정 및 이를 이용하는 소상공인 보호에 관한 규정은 전무한 상황이다. 따라서 변화하는 광고 시장을 고려하면, 반드시 온라인광고를 가장 많이 활용하고 있는 소상공인 보호 규정 등 사회적 지원체계에 대한 내용이 반영되어야 한다. 이를 기반으로 공정한 거래질서 확립 및 소비자 보호를 목적으로 하고 있는 표시광고법과의 규제 중복의 문제, 자율규제의 선언적의미보다는 입법·행정·사법적 요소를 모두 고려한 규제된 자율규제 체계의 정립, 온라인광고 중심으로 성장하고 있는 시장의 다양한 광고 형태 등을 추가적으로 논하는 것이 타당할 것이다. The advertising market is continuously growing, centered on online advertising, but there is no integrated law related to the advertising industry, and the advertising law only regulates the expression of advertisements in general. Even for each item, there are only limited regulations on expression, publication method, etc., such as the regulation of the functionality of health functional foods, and there are no regulations on the overall promotion and regulation system for the advertising industry. Accordingly, the Korea Advertising Federation has been promoting the enactment of a law on the promotion of the advertising industry, and the “Advertising Industry Promotion Act” was proposed on June 18, 2024, by Representative Kim Seung-soo. The “Advertising Industry Promotion Act” states in its reason for enactment, “The advertising industry is an industry that can lead the growth engine of our country in the 21st century, and the domestic advertising market is worth over 19 trillion won. The advertising industry is not a simple means of selling products or a sub-element of marketing, but a core industry that serves as the financial foundation for various media industries, and is also a cultural industry that is growing as an important field of cultural content. However, since there is no basic law that can define the advertising industry and systematically and comprehensively support it, the market and industry are increasingly demanding for an industrial promotion system such as research and study, human resource development, creation of a fair distribution environment, and protection of the industrial ecosystem. Accordingly, by stipulating the basic matters for the promotion of the advertising industry, we will establish a foundation for promoting advertising culture, while actively responding to changes in the market such as the development of digital technology and globalization, fostering professional human resources that meet market demands, and supporting small and medium-sized advertising companies, thereby strengthening industrial competitiveness and contributing to the development of the national economy.” It explains that the purpose is to establish a system for revitalizing and improving the advertising industry as a whole. In the absence of an integrated law related to advertising, it is welcome that such a comprehensive law for revitalizing and improving the advertising industry has been proposed. However, in the recent advertising market, online advertising has grown to be more than four times that of the existing four major media, so there is a need to break away from the framework of industry promotion and regulation centered on existing media. Online advertising is largely comprised of advertisements that reflect technical elements, such as customized advertisements, influencer advertisements, and click-based advertisements, rather than cultural content centered on production. Therefore, considering the evolving advertising market, it is essential to incorporate provisions for protecting small business owners—who are the most frequent users of online advertising—as well as related social support systems. In addition, the advertising regulatory system is comprised of advertisement self-review, self-regulation, and self-dispute resolution based on autonomy, so understanding and characteristics of the new industry must be reflected. KCI Citation Count: 0